Infection with Ehrlichia canis and Anaplasma platys (Rickettsiales: Anaplasmataceae) in two lineages of Rhipicephalus sanguineus sensu lato (Acari: Ixodidae) from Argentina - Cicuttin, Gabriel L. (2015)
Natural infection with Ehrlichia canis and Anaplasma platys in ticks belonging to the tropical and temperate lineages of Rhipicephalus sanguineus sensu lato from Argentina was evaluated. Samples were tested for Ehrlichia canis infection by PCR assays using 16S rRNA, dsb and p28 gene, while detection of A. platys was performed with 16S rRNA and groESL gene. The assignment of the ticks to each lineage was corroborated with 16S rDNA sequences. All ticks infected with E. canis and A. platys belonged to the tropical lineage. These results constitute the first record of E. canis infection in R. sanguineus s.l ticks from Argentina. No ticks from the temperate lineage were found to be infected with E. canis, coinciding with previous studies performed in Argentina and Uruguay where E. canis infection was not detected in R. sanguineus s.l from the temperate lineage. Because the presence of the tropical lineage of R. sanguineus s.l has been documented in tropical areas of northern Argentina between 22° and 24° of south latitude, the findings of this work indicate that transmission of E. canis and A. platys to dogs by R. sanguineus s.l probably occurs along this region